Organic management increases beneficial microorganisms and promotes the stability of microecological networks in tea plantation soil - Huang, Xinhui; Zheng, Yuting; Li, Panfeng; Cui, Jixiao; Sui, Peng; Chen, Yuanquan; Gao, Wangsheng (Frontiers in Microbiology, 2023)
Organic agriculture is highly regarded by people due to its principles of health, ecology, care, and fairness. The soil microbial community responds quickly to environmental changes and is a good indicator for evaluating soil microecology. Therefore, from the perspective of soil microbial communities, elucidating the impact of organic management on the soil microecology in tea plantations has a great significance for improving local tea plantation systems. The study collected bulk soil from organic management (OM)and conventional management (CM) tea plantations in Pu'er City, a major tea producing area in China, and analyzed their community diversity, structural composition, and co-occurrence networks using metagenomics technology. The results showed that compared with CM, the diversity index (Shannon) and evenness index (Heip) of soil fungi increased by 7.38% and 84.2% in OM tea plantations, . The relative abundance of microorganisms related to nitrogen cycle were increased. Specifically, there were significant increase of 47%, 2 times, 1.95 times, and 2.03 times in Rhodobiales, Nitrospirae, unclassified genus in Betaproteobacteria and Deltaproteobacteria, respectively. The relative abundance of plant residues degradation species Gemmatimonadetes, Ascomycota, Basidiomycota increased by 2.8, 1, 1.4 times respectively. . The OM was conducive to the establishment of collaborative relationships among bacterial species and increased the diversity and complexity of species relationships in fungal communities. The network stability of soil ecosystems was promoted. The organic tea plantations keystones taxa contained mycorrhizal fungi (Pezoloma_ericae, Rhizophagus_irregularis, Rhizophagus_clarus), as well as species involved in soil nitrogen metabolism (Acidobacteria_bacterium, Acidobacteriia_bacterium_AA117, Sphingomonas_sp._URHD0007, Enhydrobacter_aerosaccus), pathogen (Erysiphe_pulchra) and parasites (Paramycosporidium saccamoeba). Partial least squares method (PLS-SEM) indicated that OM impacted on N-NH4+ negatively, which increased the relative abundance of fungi, thereby positively affecting the Shannon index. In short, reasonable organic management can improve the diversity of soil microorganisms, increase the relative abundance of beneficial bacteria in tea plantation soil and promote the stability of soil microbial ecological network.